A perspectiva do trabalho autogestionado para jovens aprendizes de uma empresa de tecnologia da informação diante das possibilidades autogestionárias do software livre e aberto - Lisboa, Flávio Gomes da Silva (2022)
This qualitative, exploratory and explanatory research through a case study has as its theme the insertion of young apprentices into the world of work. The research problem consists of how to make the Solidarity Economy attractive as an alternative to insertion in the world of work for young apprentices. The hypothesis formulated is that the perspective of selfmanagement as an alternative work organization was absent in the training of young apprentices. The main question is, in a heterogestionary information technology company, how is self-management perceived by young apprentices when introduced to the Free\Libre and Open Source Software (FLOSS) development model? The secondary question is, assuming that the apprenticeship training material of the institution responsible for the theoretical training of the apprentices does not address Solidarity Economy nor Free Software, how to adapt it so that it provides them with the perception of an alternative mode of work organization? The general objective is to understand how young apprentices in a heterogeneous information technology company perceive self-management when introduced to the Free and Open Source Software development model. This research assumes that the confrontation of young apprentices with the concepts of Free Software and Solidarity Economy, connected to that of self-management, through the presentation of concrete cases of enterprises that apply these models, can change the perspective of these young people about alternatives for insertion in the world of work. The data treatment was carried out using content analysis with triangulation between the answers to the surveys, the didactic material and documents obtained through requests to the institutions involved in the professional learning program. The justifications for the production of this thesis are the filling of a gap in the research on the Solidarity Economy and the contribution to the implementation of sustainable development, which includes the eradication of poverty and the reduction of inequalities. The case study sample consisted of 11 apprentices from Serpro's regional unit in Curitiba. In general, Free Software and Solidarity Economy were referred to by the apprentices as positive ideas, but they were not part of their plans and reality. The meaning of work for the apprentices is still employment. Based on the analysis of the company's experience with Free Software, the goals of its social responsibility program, and the legal obligations, we developed a proposal for a change in the apprentices' practical training, that contributes to make self-management more attractive through the experience of developing with free and open software. In addition, we identified opportunities to improve the didactic material, so that it also contemplates the concepts of self-management, cooperative and Solidarity Economy, besides expanding the content about Free Software. We verified a precariousness in Serpro's apprenticeship program, which does not direct the practical training to activities related to the company's own business, training apprentices that the company itself would not hire as effective employees, and also for carrying out the program merely to fulfil a legal obligation.